EFFICIENCY OF THE LEWATIT MONOPLUS M 600 RESIN IN THE REMOVAL OF WATER NITRATES FOR HUMAN CONSUMPTION - Guerrero Vejarano, Tania E. (2018)
In several parts of the world the water sources are contaminated by nitrates, mainly by anthropogenic activities, being a potential threat to health, the present investigation had as objective to determine the efficiency of the conventional ion exchange resin LEWATIT MonoPlus M 600 (anionic strong base) in nitrate removal, the Uv-Vis spectroscopy method was used for the quantification of nitrates, as well as the ion exchange columns with a diameter of 1", 0.05 L of resin volume and a height of 40 cm column, where the efficiency of the ion exchange columns was evaluated, two variables were managed, the operation time and different concentrations of nitrates. It was determined that the highest efficiency of the resin was 99.55 %, at a concentration of 6.45 meq of NO3- (400 ppm) in a time of 30 min. The lowest efficiency of 18.61 % was found for the concentration of 16.13 meq of NO3- (1000 ppm) in 120 min of column operation. In the analysis of the waters of Tingo María it was determined that Well 5 of Villa Potokar was the only one that exceeds the maximum permissible limits as indicated by the national environmental water quality standards (10 ppm of NO3 of total N or 45 ppm of NO3 ) with a concentration of 52.76 ppm, therefore it is not suitable for human consumption without previous treatment.